2020
DOI: 10.1021/acs.jafc.0c02975
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Impact on Common Wheat (Triticum aestivum L.) Yield, Wholemeal Quality, and Sanitary Risk

Abstract: The rising atmospheric CO 2, concentration is expected to exert a strong impact on crop production, enhancing crop growth but threatening food security and safety. An improver wheat, a hybrid, and its parents were grown at elevated CO 2, e[CO 2 ] in open field, and their yield and rheological, nutritional, and sanitary quality were assessed. For all cultivars, grain yield increased (+16%) and protein content decreased (−7%), accompanied by a reduction in dough strength. Grain nitrogen yield increased (+24%) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
(99 reference statements)
2
16
0
Order By: Relevance
“…Along with the lowered protein concentration in grain, the composition of amino acids and their concentrations were also modified under eCO2, and the size distribution was significantly shifted towards smaller grains [5]. Blandino et al [57] also suggested a 7% decrease of protein content in four winter wheat cultivars, accompanied by a reduction in dough strength of plants grown under FACE conditions. A three-year field trial in Australia demonstrated that eCO2 consistently decreased baking quality and grain protein content in wheat, and protein composition changed towards a greater glutenin/gliadin ratio in all years [58].…”
Section: The Effects Of Eco 2 On Wheat Plants and The Mechanisms Behindmentioning
confidence: 98%
“…Along with the lowered protein concentration in grain, the composition of amino acids and their concentrations were also modified under eCO2, and the size distribution was significantly shifted towards smaller grains [5]. Blandino et al [57] also suggested a 7% decrease of protein content in four winter wheat cultivars, accompanied by a reduction in dough strength of plants grown under FACE conditions. A three-year field trial in Australia demonstrated that eCO2 consistently decreased baking quality and grain protein content in wheat, and protein composition changed towards a greater glutenin/gliadin ratio in all years [58].…”
Section: The Effects Of Eco 2 On Wheat Plants and The Mechanisms Behindmentioning
confidence: 98%
“…1881/2006, with a limit of 1750 µg kg −1 in unprocessed durum wheat) [12]. However, recent quantitative estimations have shown that increased DON contamination can be expected in cereals in certain regions in Europe as a result of future climate change [13,14]. Although the contamination of wheat grains by DON depends mainly on the meteorological conditions, particularly at flowering [15], an important role is also played by agronomic factors [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant interest in understanding the climate change-related abiotic factor impact (increased temperature, elevated CO₂, and extremes in water availability) on the relative risks of mycotoxin contamination and influences on feed/food safety and security [ 65 , 66 ]. Extreme climate conditions such as floods and droughts, which have not commonly occurred in the past, may be factors in crop contamination by various species of toxigenic fungi and related mycotoxins [ 67 , 68 ]. Fungal plant pathogens are expected to move globally and to change the diversity of diseases and pests invading essential crops with economic and social expenses.…”
Section: Mycotoxins and Climate Changementioning
confidence: 99%
“…Environmental stress has been revealed to have significant implications for mycotoxin production. Elevated CO₂ causes a consistent effect on the mycotoxin content [ 68 ]; climate change has radically influenced the global agricultural sector through restrictions in water, vegetative land, and temperature elevation that increase humidity. The high humidity raises moisture levels, enabling fungal growth and mycotoxin formation [ 71 ].…”
Section: Mycotoxins and Climate Changementioning
confidence: 99%
See 1 more Smart Citation